COVID-19 Vaccine-Related Thrombosis: A Systematic Review and Exploratory Analysis - Bilotta, Clio; Perrone, Giulio; Adelfio, Valeria; Spatola, Giovanni Francesco; Uzzo, Maria Laura; Argo, Antonina; Zerbo, Stefania (Frontiers in Immunology, 2021)
Introduction: The World Health Organization declared the COVID-19 pandemic on March 11, 2020. Two vaccine types were developed using two different technologies: viral vectors and mRNA. Thrombosis is one of the most severe and atypical adverse effects of vaccines. This study aimed to analyze published cases of thrombosis after COVID-19 vaccinations to identify patients' features, potential pathophysiologic mechanisms, timing of appearance of the adverse events, and other critical issues. Materials and Methods: The authors performed a systematic electronic search of scientific articles regarding COVID-19 vaccine-related thrombosis on the PubMed (MEDLINE) database and through manual searches. We selected 10 out of 50 articles from February 1 to May 5, 2021 and performed a descriptive analysis of the adverse events caused by the mRNA-based Pfizer and Moderna and the adenovirus-based AstraZeneca vaccine. Results: In the articles on the Pfizer and Moderna vaccines, the sample consisted of three male patients with age heterogeneity. The time from vaccination to admission was ≤3 days in all cases; all patients presented signs of petechiae/purpura at admission. In the studies on the AstraZeneca vaccine the sample consisted of 58 individuals with a high age heterogeneity and a high female prevalence. Symptoms appeared around the 9th day, and headache was the most common symptom. The platelet count was below the lower limit of the normal range. All patients except one were positive for PF4 antibodies. The cerebral venous sinus was the most affected site. Death was the most prevalent outcome in all studies, except for one study. Discussion: Vaccine-induced thrombotic thrombocytopenia (VITT) is an unknown nosological phenomenon secondary to inoculation with the Covid-19 vaccine. Several hypotheses have been formulated regarding its physiopathological mechanism. Recent studies have assumed a mechanism that is assimilable to heparin-induced thrombocytopenia, with protagonist antibodies against the PF4–polyanion complex. Viral DNA has a negative charge and can bind to PF4, causing VITT. New experimental studies have assumed that thrombosis is related to a soluble adenoviral protein spike variant,. Conclusion: Further studies are needed to better identify VITT’s pathophysiologic mechanisms and genetic, demographic, or clinical predisposition of high-risk patients.